PENGARUH PENGUATAN KELOMPOK TANI TERHADAP PARTISIPASI DAN MOTIVASI PEMUDA TANI PADA USAHA PERTANIAN DI LEUWILIANG, BOGOR - Nazaruddin Nazaruddin; Oeng Anwarudin (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2019)
Strengthening farmer groups has been carried out as an effort to regenerate farmers through fostering partner villages. The study aimed to analyze descriptively the performance of farmer group strengthening, participation and motivation of farmer youth and analyze the influence of farmer group reinforcement on farmer's youth participation and motivation in agricultural business. Research has been carried out in Leuwiliang District, Bogor Regency. The study population was farmer youth as members of farmer groups who were targeted by partner villages. The next population became the respondents of the study as many as 60 people taken by census. The research variables consisted of individual characteristics (X1), strengthening farmer groups (X 2), farmer youth participation (Y1) and farmer youth motivation (Y2). Statistical analysis used descriptive and regression statistical analysis. The results showed that the strengthening of partner farmer groups was at high criteria, participation and motivation of farmer youth was in the medium category. The participation of farmer youth is influenced by perceptions, access to ICT and strengthening farmer groups. Motivation of farmer youth is influenced by perceptions, access to ICT, strengthening farmer groups and participation in agricultural activities.